Investigating emission characteristics and plasma properties in a long-pulse magnetically insulated coaxial diode with different cathode materials. (1st March 2023) - Zhu, Danni; Cui, Yancheng; Meng, Jin; Yuan, Yuzhang; Wang, Haitao; Han, Jiangfeng
Abstract: Magnetically insulated coaxial diodes are widely used in O-type high power microwave device for intensive annular electron beam generation. This study reports on a series of electrical and optical measurements on a long-pulse magnetically insulated coaxial diodes in which the emission characteristics and the plasma properties were observed. The impact of cathode material, blade angle, diode voltage and guiding magnetic field on the emission characteristics and the plasma properties of six types of annular cathodes were studied. Two configurations of these cathodes have been used, one with a sharp edge for aluminum, bronze, graphite, stainless-steel, silicon-aluminum alloy and another metal–dielectric. The impressing diode performance was achieved with the metal-dielectric cathode characterized on the excellent emission characteristics and plasma properties. Moreover, high voltage and small blade angle are beneficial to the emission capability and emission uniformity. For the cathode with smaller blade angle, its axial plasma expansion velocity is smaller during the pulse plateau. The strong magnetic field or the large diode voltage is confirmed to reduce the axial and radial expansion velocities.